Cities drifting apart: Heterogeneous outcomes of decentralizing public education - Zelda Brutti (IZA Journal of Labor Economics, 2020)
Looking at the decentralized provision of public education in a middle-income country, this paper estimates the impact of local autonomy on service quality, finding large heterogeneity in the effect across different levels of local development. In the year 2002, Colombian municipalities were entrusted with autonomous management of their local public education based solely on a population threshold. I estimate the impact that autonomy has had on education performance across the territory, using a municipality and time fixed-effects model. I find a quality gap arising between highly developed and low-developed autonomous municipalities, in a trend that reinforces over time: the reform has induced regional inequality in education quality. I am able to support the hypothesis that autonomous and nonautonomous municipalities were on similar performance trends before decentralization was implemented, even when looking within different local development ranges. Based on the analysis of detailed municipal balance sheet data and administration indicators, I argue that local administration capacity represents the most likely explanation of why the autonomy-related discrepancies have been arising.
Keywords: I24; I25; H75; H77; 330; decentralization; education inequality; development inequality